Postmodern visual communication strategies and symbolic audience engagement on Instagram - Sya’ban, Afqira Syafa’ati; Darmawan, Ferry; Zakiah, Kiki (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
This study examines how visual communication influences audience engagement on social media through the @cianjurkuy Instagram accounts. This research departs from the lack of academic studies that comprehensively connect audience engagement data with symbolic meanings and visual communication strategies. The qualitative method was used through in-depth interviews with the creative team, observation of content uploaded in the January-March 2025 period, and digital documentation in the form of Instagram insights. The analysis was carried out using Roland Barthes' semiotics at three levels of meaning: denotation, connotation, and myth. The results show that the content @cianjurkuy culinary, tourism, and local culture—transforming simple visuals into emotional and symbolic narratives about regional identity. Audience engagement is seen through nostalgic stories, cultural pride, and a sense of community. The achievement of an engagement rate of 2.41% (above the national average of 0.98%) confirms the strength of visual strategies in building audience engagement. This study concludes that @cianjurkuy functions as a digital cultural space that strengthens social bonds and affirms collective identity through strategic visual communication.